Prevalence of congenital Syphilis at the hospital Geral de Caxias do Sul-RS among 1998-2002 - Lorenzi, Dino R.S. De; Araújo, Breno F. de; Grazziotim, Leonardo; Basso, Eliane (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: the congenital syphilis represents a challenge for public health in Brazil due to its high prevalence and harmful perinatal sequels.Objectives: to identify the prevalence of congenital syphilis carried out at a universitary hospital from south Brazil. Methods: a cross-sectional sec-tional study of all cases of congenital syphilis carried out at the Hospital Geral from Caxias do Sul University from March 1998 to august 2002.Results: the congenital syphilis coefficient was 15,5/1000 births or 120 cases in 8009 births. Prenatal care was confirmed by of 78,4% of the studiedpregnant women. In 38,4%, the maternal syphilis diagnosis was obtained only after the delivery. The main causes of failure in the prenatal preventionof congenital syphilis were: lack of treatment for the pregnant woman (14,9%) or her partner (53,2%), inappropriate mother treatment (22,3%) or atreatment completion not prior to 30 days of delivery (28,7%). The low birth weight rate was of 29,1%, while the perinatal mortality rate was 1.2deaths each 1000 deliveries. Conclusion: the results above indicate that the majority of the studied congenital syphilis cases resulted from prenatalcare failures.